THE IMPACT OF CORPORATE GOVERNANCE STRUCTURE ON THE EXTERNAL AUDIT FEE IN SHARIA SHARES - Abdul Rasid (Jurnal Ekonomi dan Bisnis Airlangga, 2021)
Introduction: This study aims to determine the impact of corporate governance structures on external fees in sharia stocks that are consistently listed in JII in 2013-2018.Methods: The number of samples in this study recorded 12 consistent sharia stocks listed in the years 2013-2018. This study uses a quantitative approach with panel data analysis method.Results: The results show that the average size of the board of commissioners is six to seven people, the average size of the board of directors is seven to eight people, the average size of the audit committees is three to four people, and the average size of the internal audit is fifteen to sixteen people. The hypothesis test shows that variables which have a significant impact on the audit fee are the size of the board of commissioners and the internal audit. Meanwhile, the size of the board of directors and the audit committees do not have a positive impact on audit fees.Conclusion and suggestion: Companies use more funding from debt than their own capital. Judging from the liquidity ratio, it shows that the company is in a liquid state, which is very capable of fulfilling obligations or debts that must be immediately paid by the company.